PENGARUH KUALITAS PELAYANAN, HARGA, DAN LOKASI TERHADAP KEBERHASILAN USAHA (Studi Kasus Pada Es Jeruk Akang Jln. Cendrawasih Kelurahan Pasir Putih, Kecamatan Jambi Selatan, Kota Jambi) - Rahma Deni Putri Haimda; Nurnadia; Ratih Kusumastuti (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
This study aims to analyze the influence of service quality, price and the location of the success of the Akang Squeeze Orange Ice business in JIn.Cendrawasih, Pasir Putih Village, South Jambi District, Jambi City. The sampling method used is purposive sampling method. The sample in this study were 98 customers from Akang Peras Jeruk Peras and then an analysis was carried out on the data obtained using quantitative and qualitative data. Methods of data collection by conducting interviews, questionnaires, and observation. Testing the hypothesis using the t test shows that the three independent variables studied proved to have a significant partial effect on the dependent variable of business success.